Neo-Muʻtazilismus? : Intention und Kontext im modernen arabischen Umgang mit dem rationalistischen Erbe des Islam - Hildebrandt, Thomas, 1968- (Islamic Philosophy, Theology and Science. Texts and Studies, 2007)
This book examines the modern Arab rediscovery of the Muʿtazila through a critical assessment of the concept of \'Neo-Muʿtazilism\' and by concentrating on the various intentions and contexts of the use of Muʿtazilite ideas. The main part of the book analyzes five ways of understanding Mu'tazilite ideas - liberal, historic-materialist, political-Islamic, literary-exegetical and through comparison with the philosophie des valeurs - as well as one way of dealing with the school historically: the treatment of the miḥna . The book discusses a wide range of authors of whom many, such as Aḥmad Amīn, Ḥusain Murūwa, Ḥasan Ḥanafī, Muḥammad ʿAmāra, Naṣr Abū Zaid und Muḥammad ʿĀbid al-Ğābirī, have had an important impact on modern Arab-Islamic thought. By also presenting authors such as Zuhdī Ğārallāh, Chikh Bouamrane, Rašīd al-Ḫayyūn, Amīn Nāyif Ḏiyāb, Samīḥ Duġaim, ʿĀdil al-ʿAwwā und Fahmī Ğadʿān, additional light is shed on a number of lesser known figures.